Pastor Paroki Dan Tanggung Jawabnya Menurut Ketentuan Kitab Hukum Kanonik 1983 - Blasius Superma Yese; Alfonsus Ara (Jurnal Magistra, 2024)
Parish is a term used within the Catholic Church to refer to a particular community of believers. The community of faith is entrusted to a specific priest appointed by the diocesan bishop. The parish priest is the shepherd for the people in the parish. Parish priests are given duties and responsibilities, which are regulated in the legal provisions of the Catholic Church.A good and in-depth understanding of the community of believers in the parish and of the duties and responsibilities entrusted to the parish priest is expected to help priests to be able to carry out their pastoral duties properly and correctly. In this way, the faithful will grow well. This article provides several important notes regarding the parish priest and his duties or responsibilities according to the provisions of the Code of Canon Law 1983.